Complications of Ultrasound Guided Renal Biopsy in 100 Children: Experience at a Tertiary Care Hospital - Quader, Mohammed Maruf Ul; Biswas, Susmita; Datta, Mitra; Chowdhury, Muhammad Jabed Bin Amin; Haque, Salina; Mohammad Moinuddin, Kazi; Sen, Sunanda; Bappy, Sawrav Deb (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background: Use of automated device with ultrasound guidance in renal biopsy has improved the adequacy and reduced the complication. Chittagong Medical College Hospital (CMCH) is a tertiary teaching hospital where Pediatric Nephrology Department started its journey on 11th December 2013. Since then renal biopsy is going on. Aim of the study is to see the rate of adequacy and complication of renal biopsy along the course of years. Materials and methods: This is a retrospective study carried on 100 consecutive ultrasonography guided percutaneous renal biopsy from lower pole of left native kidney performed by the pediatric nephrologist. All hospitalized children aged up to 12 years admitted since 2014 were included. Spring loaded automated biopsy needle was used in 88% cases and Trucut biopsy needle in 12% cases. Results: Most of the patients were aged between 1 to 10 years with male female ratio 0.9:1. Midazolam was used for sedation in all patients except one who needed general anesthesia. Light microscopy and Direct Immunofluorescence (DIF) report was made but no facility for electron microscopy. Gross hematuria was experienced in 5% cases and one case needed blood transfusion. There was one case with blood clot in urinary bladder causing dysuria but no urinary retention was observed. Post biopsy perinephric hematomas developed in 4 cases. Number of needle passes to obtain adequate biopsy material in native kidney was £3 in 78% cases. Adequate specimen was found in 95% cases. Conclusion: Percutaneous renal biopsy can be done adequately and safely in resource poor setup if pediatric nephrologist and radiologists are available. Chatt Maa Shi Hosp Med Coll J; Vol.19 (2); July 2020; Page 9-12